THE LINGUOCOGNITIVE ASPECTS OF PROVERB RESEARCH (TAMADDUN NURI JURNALI, 2024)
This article examines the linguocognitive aspects of proverb research. Based on the theory of cognitive metaphor, everyday language possesses a metaphorical structure. Metaphor is a solid and integral part of our everyday language. Its main function is to reveal abstract representations through concrete experiences. For cognitive metaphor theory, metaphors that correspond to metaphorical concepts are of interest, thereby demonstrating their systematicity.